Study on Supported Metal Catalysts for Hydrogen Production from Coal Slurry Pyrolysis - Zhang, Lei; Zhang, Lixin; Shu, Xinqian; Zhang, Lei (Asian Journal of Chemistry, 2013)
The objective of this paper is to study the effect of supported metal catalysts on hydrogen production from coal slurry pyrolysis and to explain their catalytic mechanism. Experimental results show that Ag/g-Al2O2 and Fe/g-Al2O3 have good catalytic activity at 700 ºC to 1100 ºC with the higher yield of H2 being mainly resulted from the phenomenon of hydrogen spillover. Ni/g-Al2O3 shows good catalytic activity at both medium temperature and higher temperature. Because Co inhibits the activity of catalyst, the Co/g-Al2O3 shows good catalytic activity only at medium temperature. The characteristic diffraction peaks of Cd/g-Al2O3, Zn/g-Al2O3 and Cu/g-Al2O3 are CdO, ZnO and CuO, respectively. These three oxides are n-type oxides, so they show better catalytic activity at medium temperature.